Stuck in Sharia Space: The Experiences of Christian Students to Reside in Langsa, Aceh - Yogi Febriandi; Yaser Amri (Al-Jami'ah: Journal of Islamic Studies, 2021)
This article examines the problem of spatial access for Christian students of Samudera University as experiences of minorities in Langsa, Aceh. This article argues that Aceh’s public space that is formed by religious identity, leads dichotomy of citizenship in social life. Using life story method, this article explores the problem of Christian students of Samudera University to reside in Langsa. The results show the formation of space by displaying a single identity has polarized majority-minority in public space. Finally, this article also shows that the formation of space by displaying a single identity created an imbalance space for minority, and compelling minority to create alternative space.[Artikel ini membahas persoalan akses ruang berdasarkan pengalaman mahasiswa minoritas Kristen di Universitas Samudera, Langsa, Aceh. Artikel ini berargumentasi bahwa ruang publik Aceh terbentuk oleh identitas religius yang berujung pada dikotomi kehidupan sosial penduduknya. Dengan pendekatan life story, artikel ini menjelaskan masalah yang dihadapi mahasiswa Kristen yang tinggal di Langsa, Aceh. Dalam kesimpulannya menunjukkan bahwa formasi ruang publik terbelah dan tidak seimbang antara identitas mayoritas dan minoritas, dimana identitas minoritas terdesak untuk menciptakan ruang alternatif baru.]